Integrated Climate Security Programming in Climate Finance: An Analysis of Multilateral Climate Funds - Scartozzi, Cesare M.; Savelli, Adam; Meddings, George; Pacillo, Grazia; Läderach, Peter R.D. (2022)
Conflict and climate change can be linked via several pathways which may deepen insecurity, including the erosion of livelihoods, displacement, and increased vulnerability to climate shocks. Climate finance presents a possible method to negate the links between climate change and conflict, yet questions surround the efficacy of financial mechanisms to tackle these issues. This study provides a comprehensive overview of the state of climate finance and its intersections with peace and security. The paper asks if the allocation of resources is consistent with the climate security priorities of recipient countries, and if investments in climate-vulnerable and politically fragile contexts have sufficient elements of integrated climate security programming ‒ i.e., dual climate action and peacebuilding objectives. To answer these questions, the study looks at 22 multilateral climate funds and their respective USD 28.3 billion financial allocations. Then, using an automated content analysis, the paper analyzes conflict sensitivity in projects occurring in 37 countries with a significant history of conflict compounded with high levels of climate vulnerability. The findings of the study show that there are significant gaps and lapses in the allocation of funding as well as in the operationalization of integrated climate security programming. As a result, it is argued, multilateral climate funds are exposed to unforeseen security and political risks, which can undermine the sustainability of investments. Overall, the paper generates novel insights and data on climate finance, providing actionable outputs on how to better use climate investments to support peace.